2010
DOI: 10.2139/ssrn.1660970
|View full text |Cite
|
Sign up to set email alerts
|

Throwing Foreign Aid at HIV/Aids in Developing Countries: Missing the Target?

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 34 publications
(14 reference statements)
0
2
0
Order By: Relevance
“…In one study, health aid is found to have no sig‐nifcant effect on immunization coverage, life expectancy, death rate, or infant mortality, while another study finds a significant positive effect on infant mortality . other research has found significant positive effects of health sector aid on DPT3 (diphtheria, pertussis, and tetanus) immunization coverage in countries with low corruption control, of U.S. aid in reducing AIDS‐related deaths (although aid in general did not reduce new HIV infections), and of aid for malaria in increasing the distribution of insecticide‐treated mosquito nets and in reducing mortality rates among children under fve years of age in sub‐Saharan African countries …”
Section: The Dah Systemmentioning
confidence: 98%
“…In one study, health aid is found to have no sig‐nifcant effect on immunization coverage, life expectancy, death rate, or infant mortality, while another study finds a significant positive effect on infant mortality . other research has found significant positive effects of health sector aid on DPT3 (diphtheria, pertussis, and tetanus) immunization coverage in countries with low corruption control, of U.S. aid in reducing AIDS‐related deaths (although aid in general did not reduce new HIV infections), and of aid for malaria in increasing the distribution of insecticide‐treated mosquito nets and in reducing mortality rates among children under fve years of age in sub‐Saharan African countries …”
Section: The Dah Systemmentioning
confidence: 98%
“…As noted in Nunnenkamp and Öhler (2011), the identifying assumption of the DDD estimator is that, in the absence of the treatment, the difference in the change of private donations as our dependent variable between the two periods before and after the tsunami would have been the same, on average, for the treatment group of NGOs with (wider) operations in the affected region and the control group of NGOs without (or with narrower) operations. The plausibility of this assumption is debatable if the treatment and control groups differ from each other in other respects that might be associated with the dynamics of the dependent variable (Abadie, 2005).…”
Section: Extensions and Robustness Tests: Ddd Analysismentioning
confidence: 99%